2019
DOI: 10.1097/shk.0000000000001162
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline Phosphatase Activity and Endotoxemia After Infant Cardiothoracic Surgery

Abstract: Endotoxemia is common in infants undergoing CPB. Native AP activity and endotoxemia are inversely related and ex vivo addition of exogenous AP reduces whole blood EAA. Future research should evaluate AP as a therapy to reduce the harmful effects of endotoxemia following infant CPB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Finally, duration of mechanical ventilation would indicate worsening disease severity and also lead to increased central pressures, venous congestion, and subsequent intestinal edema and injury. Alternatively, the intestinal injury and subsequent endotoxin leak could cause direct lung injury and cause longer duration of mechanical ventilation (52,53). Our data confirm the previous finding in Typpo et al (26) that CPB time and vasopressor use are associated with higher postoperative IFABP, but the remainder of the associations are novel in a pediatric population.…”
Section: Clinical Factors Associated With Higher Post-operative Ifabpsupporting
confidence: 87%
“…Finally, duration of mechanical ventilation would indicate worsening disease severity and also lead to increased central pressures, venous congestion, and subsequent intestinal edema and injury. Alternatively, the intestinal injury and subsequent endotoxin leak could cause direct lung injury and cause longer duration of mechanical ventilation (52,53). Our data confirm the previous finding in Typpo et al (26) that CPB time and vasopressor use are associated with higher postoperative IFABP, but the remainder of the associations are novel in a pediatric population.…”
Section: Clinical Factors Associated With Higher Post-operative Ifabpsupporting
confidence: 87%
“…These enzymes are well established as biomarkers of liver and bone disease, but their physiologic roles remain incompletely understood. Recent evidence points towards a potential protective effect of AP in the mitigation of AKI through dephosphorylation of nephrotoxic molecules including extracellular adenine nucleotides 2426 and endotoxin 2729 . Phase 2 human studies have demonstrated efficacy of AP in the treatment of sepsis-induced AKI 3032 .…”
Section: Introductionmentioning
confidence: 99%
“…TNAP is the dominant circulating isoenzyme and has been successfully used as a biomarker of liver and bone disease [17]; however, its physiological role is not fully understood. Recently, APs have been shown to dephosphorylate and detoxify two key pathologic molecules thought to contribute to inflammation and organ injury after both cardiac surgery and sepsis: bacterial-derived lipopolysaccharide (LPS-endotoxin) [10,[18][19][20][21][22][23][24][25] and extracellular adenine nucleotides (ATP, ADP, and AMP) released during cellular necrosis or apoptosis [26][27][28][29][30]. AP removes one phosphate group from the conserved lipid A moiety of LPS resulting in a monophosphoryl product with reduced toxicity [21,31].…”
Section: Introductionmentioning
confidence: 99%